The Impact of Gendered Labor Migration on Children’s Growth: A Case of Indramayu Regency, West Java Province, Indonesia - Titan Listiani (Research Centre for Population, Indonesian Institute of Sciences, 2018)
Men and women have different roles in the household. Traditionally, men are the breadwinners and women are the caretakers of the household. Therefore, the absence of a father or a mother will bring some effects on the family left behind. By focusing on the impact of parental migration on young children, this paper examines how the absence of a father or a mother may differently influence children’s growth. The paper also evaluates the role of the Integrated Health Service Post (Pos Pelayanan Terpadu, henceforth Posyandu - a community assistance service for health improvement in Indonesia) in children’s growth. The survey was conducted in Indramayu Regency, one of the regions in Indonesia with the highest percentage of labor migrants. BNP2TKI reported that more than 131 thousand migrants were departing from Indramayu between 2011 and 2015. The indicator of children’s growth in this study used the anthropometric measurements based on the 2006 WHO growth standards. This study finds that gendered labor migration tends to have different impacts on children. Father’s migration tends to influence the children’s growth positively. However, mother’s migration has not been found to be as an influential factor since the advantage of remittances is canceled out by the absence of mothers. The findings also show that Posyandu plays a significant role in improving the growth of children and can be an effective strategy to reduce undesired effects of migration on them.